IB - "Jongeward, Dorothy." (California, 1977)
Relationships are at the heart of every positive human experience. Maxwell, a master communicator and relational expert, makes learning about relationships accessible to everyone. The most sophisticated leaders and salespeople will pick up on skills that will make them even better, and relational novices will learn skills that can transform them into relational dynamos.
Keywords: Transactional Analysis